Geopolitical Implications of the Russia-China Nexus: Power Dynamics and Regional Impact in Central Asia (2003-2023) - Roy, Nadeem Abbas; Shahzad, Sajid Mehmood (Annals of Human and Social Sciences, 2025)
The Russia-China strategic cooperation, spanning from 2003 to 2023, has been making a significant impact on Central Asia's geopolitical landscape. The abundant energy resources and commercial routes of the region further make focus of their collaboration. The study analyzed Central Asia's power dynamics and alliance formations, the economic and security ramifications of multilateral institutions, and the broader implications of the alliance's growing regional and global prominence. Both, standard and emergent approaches with inductive technique were employed to integrate the literary studies with international concepts, which offers a detailed understanding of emerging patterns and their regional implications. A thematic analysis assesses the geopolitical, economic, and security aspects of the Russia-China alliance. Understanding these dynamics is vital for assessing the changing character of regional geopolitics in Central Asia, the rapid nature of the alliance, and the significant consequences to the United States of America.